2018
DOI: 10.1111/dme.13616
|View full text |Cite
|
Sign up to set email alerts
|

Age distribution and metabolic disorders in people with Type 1 diabetes in Beijing and Shantou, China: a cross‐sectional study

Abstract: Compared with the general population, people with Type 1 diabetes comprised more young and fewer elderly individuals. The prevalence of metabolic syndrome in the Type 1 diabetes population was 10.1%. Hypertension and dyslipidaemia were more prevalent in obese than non-obese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
(59 reference statements)
5
14
3
Order By: Relevance
“…The prevalence of MetS in our survey was similar to that reported in the Action LADA study in Europe (9). Differently, the prevalence of MetS in T1DM in our survey was much higher than the 10.1% in T1DM reported in a previous Chinese survey ( n = 849) (27). Given that the prevalence of MetS increases with increasing age (28), and the much younger age of T1DM patients in that Chinese survey (the median age: 22 years) (27), the observed high prevalence of MetS in our patients is not at odds with the findings of that Chinese survey.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The prevalence of MetS in our survey was similar to that reported in the Action LADA study in Europe (9). Differently, the prevalence of MetS in T1DM in our survey was much higher than the 10.1% in T1DM reported in a previous Chinese survey ( n = 849) (27). Given that the prevalence of MetS increases with increasing age (28), and the much younger age of T1DM patients in that Chinese survey (the median age: 22 years) (27), the observed high prevalence of MetS in our patients is not at odds with the findings of that Chinese survey.…”
Section: Discussioncontrasting
confidence: 93%
“…Differently, the prevalence of MetS in T1DM in our survey was much higher than the 10.1% in T1DM reported in a previous Chinese survey ( n = 849) (27). Given that the prevalence of MetS increases with increasing age (28), and the much younger age of T1DM patients in that Chinese survey (the median age: 22 years) (27), the observed high prevalence of MetS in our patients is not at odds with the findings of that Chinese survey. Using age at diagnosis ≥30 years as one of the inclusion criteria and the CDS criteria for definition of MetS, which was more appropriate for Chinese population for cardiovascular risk assessment (18), our survey generated a more reliable estimation of the prevalence of MetS in newly diagnosed diabetes.…”
Section: Discussioncontrasting
confidence: 93%
“…(1) Fasting plasma glucose (FPG), LDL, HDL, and TG levels were analyzed at the Youanmen Center for Clinical Laboratory at Capital Medical University using the enzymatic colorimetric tests, and serum uric acid (SUA) levels were analyzed using the urinalysis (UA) plus method. We classified TG levels into 2 categories: ≥ 150 mg/dL and < 150 mg/dL, a categorization widely used in previous studies [29, 30]. (2) BP was measured 3 times at intervals of 45 seconds with a sphygmomanometer.…”
Section: Methodsmentioning
confidence: 99%
“…The global incidence of T1D is reported to be increasing at a rate of 3% each year (Rahelic, ). In China, where the population includes a large proportion of young individuals, many people suffer from T1D (Huo et al, ). Optimal glycaemic control during adolescence yields long‐term benefits into adulthood (Carlsen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies showed that youths are at increased risk for suboptimal glycaemic control (Hartl, Seiffge-Krenke, & Laursen, 2015;Schwandt et al, 2017). According to studies from mainland China, youth had an average HbA 1c ranging from 8.25%-9.2% and more than 50% of these youth failed to achieve the goal of glycaemic control, namely, HbA 1c below 7.5% (Huo et al, 2018;McGuire et al, 2017;Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%